(untitled) (Research, Society and Development, 2021)
Expenses with food stand out as the factor with the greatest impact of poultry production costs, and in times of increase in the price of commercialization of the main inputs such as corn and soybean meal, it is common to search for alternative foods that can provide lower production costs and provide an adequate supply of nutrients. Among the alternative foods, the co-products of ethanol production obtained from cereals grains, which are promising substitutes in poultry diets, due to high content of crude protein, aminoacids, energy and mineral levels. Differences in the nutritional composition of the grains, and the processing methods for obtaining ethanol and drying may lead to variations in the nutritional composition, and consequently, in the availability of nutrients in the co-products. In this way, several studies have been carried out to determine the nutritional values present in the various co-products used in animal feed, aiming at formulations of increasingly accurate feeds. The high variability, concentration and quality of nutrients between the different sources of co-products, cause great divergences in relation to the levels of inclusion of these co-products recommended by nutritionists for poultry diets. The objective of this literature review is to highlight the nutritional composition and the use of corn ethanol co-products in poultry feed, as an economically viable alternative food for poultry production.